PUPPET PICTURES AS STORYTELLING MEDIA TO TEACH ENGLISH VOCABULARY FOR YOUNG LEARNERS - Lutfiana (Faculty of Social, Economics and Humanities, 2021)
English foreign learners are diverse in age, level, and grade. These different characteristics become essential in the field of teaching and learning. It is effective for reference in choosing the applicable media or techniques for teaching and learning. Here, this study concerns describe the relevant media to teach vocabulary to young learners, exclusively where the first language (L1) of the plurality of the learners are not Native-English. Due to young learners learn English as a foreign at the beginner level, the learning strategies and teaching media which are given by teachers should be appropriate with them. Teachers have to develop their ideas in electing suitable media to teach young learners. Then, this paper, based on reviews of literature, explores the use of Puppet Pictures as storytelling media to teach young learners. Puppet Pictures is one of the interactive media which can persuade young learners to attend with the learning. The result indicates that the Puppet picture is able to allow the learners’ attention to the lesson. It can be played through a story. It helps young learners understand the new vocabularies by seeing the real objects and acquiring the learning process.